Cryptic and ubiquitous aplastidic cryptophytes are key freshwater flagellated bacterivores - Šimek, Karel; Mukherjee, Indranil; Szöke-Nagy, Tiberiu; Haber, Markus; Salcher, Michaela M; Ghai, Rohit (The ISME journal, 2023)
Morphology-based microscopic approaches are insufficient for a taxonomic classification of bacterivorous heterotrophic nanoflagellates (HNF) in aquatic environments since their cells do not display reliably distinguishable morphological features. This leads to a considerable lack of ecological insights into this large and taxonomically diverse functional guild. Here, we present a combination of fluorescence in situ hybridization followed by catalyzed reporter deposition (CARD-FISH) and environmental sequence analyses which revealed that morphologically indistinguishable, so far largely cryptic and uncultured aplastidic cryptophytes are ubiquitous and prominent protistan bacterivores in diverse freshwater ecosystems. Using a general probe for Cryptophyceae and its heterotrophic CRY1 lineage, we analyzed different water layers in 24 freshwater lakes spanning a broad range of trophic states, sizes and geographical locations. We show that bacterivorous aplastidic cryptophytes and the CRY1 lineage accounted for ca. 2/3 and ¼ of total HNF, respectively, in both epilimnetic and hypolimnetic samples. These heterotrophic cryptophytes were generally smaller and more abundant than their chloroplast-bearing counterparts. They had high uptake rates of bacteria, hinting at their important roles in channeling carbon flow from prokaryotes to higher trophic levels. The worldwide ubiquity of Cryptophyceae and its CRY1 lineage was supported by 18S rRNA gene sequence analyses across a diverse set of 297 freshwater metagenomes. While cryptophytes have been considered to be mainly plastidic "algae", we show that it is the aplastidic counterparts that contribute considerably to bacterial mortality rates. Additionally, our results suggest an undiscovered diversity hidden amongst these abundant and morphologically diverse aplastidic cryptophytes.
Keywords: Heterotrophic Processes; Phylogeny; ekosystém; In Situ Hybridization, Fluorescence; Bacteria; heterotrofní procesy; jezera; Ecosystem; hybridizace in situ fluorescenční; fylogeneze; Cryptophyta; Lakes